2012
DOI: 10.1682/jrrd.2010.10.0210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robot-assisted therapy on stroke rehabilitation in upper limbs: Systematic review and meta-analysis of the literature

Abstract: Abstract-We systematically reviewed and analyzed the literature to find randomized controlled trials (RCTs) that employed robotic devices in upper-limb rehabilitation of people with stroke. Out of 574 studies, 12 matching the selection criteria were found. The Fugl-Meyer, Functional Independence Measure, Motor Power Scale, and Motor Status Scale outcome measures from the selected RCTs were pooled together, and the corresponding effect sizes were estimated. We found that when the duration/intensity of conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
199
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(232 citation statements)
references
References 36 publications
7
199
2
5
Order By: Relevance
“…A robot-assisted therapy has many advantages over hands-on, manual therapy. Robotic systems can monitor movements and measure motor skills and can deliver coherent training during each session [2] [3]. Advances in robotic technology have resulted in the development of several advanced active robotic systems for upper limb post-stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…A robot-assisted therapy has many advantages over hands-on, manual therapy. Robotic systems can monitor movements and measure motor skills and can deliver coherent training during each session [2] [3]. Advances in robotic technology have resulted in the development of several advanced active robotic systems for upper limb post-stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies prove that arm therapy has positive effects on the rehabilitation progress of stroke patients [1][2][3][4][5][6][7]. So, the interested in using the robotic device to help rehabilitation therapy is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that using robotic devices in rehabilitation process on stroke patients has positive effects [3][4][5][6][7]. However, there are a few types of research and developments about using robot for rehabilitation in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] In other cases, assistive robotics may prime the neuromusuloskeletal system to move, initiating the potential to recover normal voluntary movements. 38 In summary, the brain is soft wired. Neuroplasticity is a process which can continue across the lifespan when paired with positive life style behaviors, dynamic learning and physical activities.…”
Section: Introductionmentioning
confidence: 99%